Magnetic resonance: an introduction to ultrashort TE (UTE) imaging. - Robson, M; Gatehouse, P; Bydder, M; Bydder, G (2003)
The background underpinning the clinical use of ultrashort echo-time (UTE) pulse sequences for imaging tissues or tissue components with short T2s is reviewed. Tissues properties are discussed, and tissues are divided into those with a majority of short T2 relaxation components and those with a minority. Features of the basic physics relevant to UTE imaging are described including the fact that when the radiofrequency pulse duration is of the order T2, rotation of tissue magnetization into the transverse plane is incomplete. Consequences of the broad line-width of short T2 components are also discussed including their partial saturation by off-resonance fat suppression pulses as well as multislice and multiecho imaging. The need for rapid data acquisition of the order T2 is explained. The basic UTE pulse sequence with its half excitation pulse and radial imaging from the center of k-space is described together with options that suppress fat and/or long T2 components. Image interpretation is discussed. Clinical features of the imaging of cortical bone, tendons, ligaments, menisci, and periosteum as well as brain, liver, and spine are illustrated. Short T2 components in all of these tissues may show high signals. Possible future developments are outlined as are technical limitations.